The Impact of Location and Price Perception on Customer Loyalty - Mezafrie, Hilda Michelle; Supriyono (Jurnal Economic Resource, 2025)
The culinary MSME sector has shown significant growth in major cities such as Surabaya, driven by high consumer demand for affordable and accessible food services. This study aims to analyze the influence of location and price perception on customer loyalty at Dapur Bu Hepy in Surabaya. This is a quantitative study using a questionnaire distributed to 96 respondents. The data were analyzed using Structural Equation Modeling (SEM) based on Partial Least Square (PLS). The results show that both location and price perception have a positive and significant effect on customer loyalty, with price perception contributing the strongest influence. The most dominant indicator within the price perception variable is price competitiveness, which is considered the main reason customers remain loyal to Dapur Bu Hepy.